Participants’ perception of pharmaceutical clinical research: a cross-sectional controlled study - González-Saldivar, Gerardo (Patient Prefer Adherence, 2016)
BACKGROUND: There is scarce scientific information assessing participants’ perception of pharmaceutical research in developed and developing countries concerning the risks, safety, and purpose of clinical trials. METHODS: To assess the perception that 604 trial participants (cases) and 604 nonparticipants (controls) of pharmaceutical clinical trials have about pharmaceutical clinical research, we surveyed participants with one of four chronic diseases from 12 research sites throughout Mexico. RESULTS: Participation in clinical trials positively influences the perception of pharmaceutical clinical research. More cases (65.4%) than controls (50.7%) perceived that the main purpose of pharmaceutical research is to cure more diseases and to do so more effectively. In addition, more cases considered that there are significant benefits when participating in a research study, such as excellent medical care and extra free services, with this being the most important motivation to participate for both groups (cases 52%, controls 54.5%). We also found a sense of trust in their physicians to deal with adverse events, and the perception that clinical research is a benefit to their health, rather than a risk. More controls believed that clinical trial participants’ health is put at risk (57% vs 33.3%). More cases (99.2%) than controls (77.5%) would recommend participating in a clinical trial, and 90% of cases would enroll in a clinical trial again. CONCLUSION: Participation in clinical trials positively influences the perception that participants have about pharmaceutical clinical research when compared to nonparticipants. This information needs to be conveyed to clinicians, public health authorities, and general population to overcome misconceptions.